Effect of Gender, Migration, and Family Support on Socio-Economic Well-Being of Nepalese Youth - Hatawal, Prabha (The Batuk, 2024)
This study explored the interplay between gender dynamics, migration experiences, and family support and their impact on the socio-economic well-being of Nepali youth. A structured questionnaire was administered to 384 Nepali youth aged 18-34 years using a convenience sampling design. With the diversified participant profile, the descriptive analysis found that there is negative impact of traditional gender norms on welfare, while migration experiences and strong family support had positive socio-economic effects. Empirical correlations supported the hypotheses, emphasizing the need for gender-specific interventions and policies. The study advocates for approaches that consider migration experiences, family support, and the reconfiguration of traditional gender roles. It provides valuable insights for policymakers and practitioners, emphasizing the importance of addressing gender inequalities, formulating migration policies, and strengthening family support systems. Specific strategies, including counseling programs and services, are necessary to alleviate the socio-economic challenges faced by Nepali youth. The study offers a framework for designing effective programs and interventions that consider the complex relationship between gender development, migration experiences, family support, and the socio-economic well-being of Nepali youth.